Managing the information revolution: library management, the control of prescriptive technologies, and the future of librarianship - Sierpe, Eino (Library Management, 2004)
This article seeks to promote a critical perspective on the present conceptualization of library management and the problems posed by technology. More specifically, it addresses the challenges faced by library administrators in relation to computing technologies. Through the adoption of Ursula Franklin's view of technology as “practice”, the article contrasts the practice of holistic and prescriptive technologies in library contexts. It also addresses the transformations of librarianship and the increasing adoption of prescriptive technological models. To exemplify the ongoing destruction of traditional librarianship, the three practices that comprise the fundamentals of librarianship are analyzed, namely, cataloging, collection development, and reference work. © 2004, Emerald Group Publishing Limited
Keywords: Information management; Librarianship; Libraries; dept.ils